Dealing with Black Swan Events: An Interview with Vijay Mahajan, Founder and CEO of Basix1. (23rd September 2016) - Ashta, Arvind
Abstract : Social entrepreneurs who are genuinely following their mission may find unexpected disaster if the industry as a whole does not conform to the social consciousness created by their image.